PERCEPTIONS OF ACCOUNTING STUDENTS REGARDING ACCOUNTING RULE ADHERENCE, UNETHICAL BEHAVIOR, AND INDIVIDUAL MORALITY TOWARDS ACCOUNTING FRAUD WITH INTERNAL CONTROL AS MODERATION - Pradasiwi, Arda Walika; Rahayu, Ruci Arizanda; Ramadhani, Novia Eka Putri; Ruma'Isya, Ninik (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to examine the perceptions of accounting students regarding the effect of adherence to accounting rules, unethical behavior, and individual morality on accounting fraud with internal control as a moderator. Method: The research method used is quantitative with a population of active students of accounting study programs at Muhammadiyah Sidoarjo University. Results: The results showed that the observance of accounting rules had no effect on accounting fraud, unethical behavior and individual morality had a significant effect on accounting fraud, and internal control moderated the relationship between the observance of accounting rules and unethical behavior on accounting fraud. Novelty: This study provides insights into the moderating role of internal control in the relationship between adherence to accounting rules, unethical behavior, and accounting fraud, highlighting the significant impact of individual morality on fraudulent practices.